f(x) = e^(lne^(2x^(2))+3
f(x) = e^(ln(x)+8)
f(z) = e^(ln(9))
can someone show me how to do these ones, so i can see the answers...much thanks...
mathaction
Brackets, there is no way of being sure what this means as:
1. The brackets you do have don't match
2. Because of missing brackets there is no way of telling what the "ln" is
being applied to.
I will assume (probably incorrectly) that you mean:
$\displaystyle
f(x) = e^{\ln(e^{2x^2}+3)}=e^{2x^2}+3
$
(since $\displaystyle e^{\ln(g)}=g$) Now use the chain rule:
$\displaystyle
f'(x)=4x e^{2x^2}
$
RonL